Impact of compressed air energy storage demands on gas turbine performance - Igie, Uyioghosa; Abbondanza, Marco; Szymański, Artur (Sage, 2020)
Industrial gas turbines are now required to operate more flexibly as a result of incentives and priorities given to renewable forms of energy. This study considers the extraction of compressed air from the gas turbine; it is implemented to store heat energy at periods of a surplus power supply and the reinjection at peak demand. Using an in-house engine performance simulation code, extractions and injections are investigated for a range of flows and for varied rear stage bleeding locations. Inter-stage bleeding is seen to unload the stage of extraction towards choke, while loading the subsequent stages, pushing them towards stall. Extracting after the last stage is shown to be appropriate for a wider range of flows: up to 15% of the compressor inlet flow. Injecting in this location at high flows pushes the closest stage towards stall. The same effect is observed in all the stages but to a lesser magnitude. Up to 17.5% injection seems allowable before compressor stalls; however, a more conservative estimate is expected with higher fidelity models. The study also shows an increase in performance with a rise in flow injection. Varying the design stage pressure ratio distribution, brought about an improvement in the stall margin utilized, only for high extraction.
Keywords: gas turbine; Compressed air; energy storage; extraction; Injection; Stall